GPD1 specifically marks dormant glioma stem cells with a distinct metabolic profile - Rusu, Patricia M.; Döring, Kristina; Dettling, Steffen; Tschaharganeh, Darjus-Felix; Bukau, Bernd; Kramer, Günter; Herold-Mende, Christel (Cell stem cell, 2019)
Summary - Brain tumor stem cells (BTSCs) are a chemoresistant population that can drive tumor growth and relapse, but the lack of BTSC-specific markers prevents selective targeting that spares resident stem cells. Through a ribosome-profiling analysis of mouse neural stem cells (NSCs) and BTSCs, we find glycerol-3-phosphate dehydrogenase 1 (GPD1) expression specifically in BTSCs and not in NSCs. GPD1 expression is present in the dormant BTSC population, which is enriched at tumor borders and drives tumor relapse after chemotherapy. GPD1 inhibition prolongs survival in mouse models of glioblastoma in part through altering cellular metabolism and protein translation, compromising BTSC maintenance. Metabolomic and lipidomic analyses confirm that GPD1+ BTSCs have a profile distinct from that of NSCs, which is dependent on GPD1 expression. Similar GPD1 expression patterns and prognostic associations are observed in human gliomas. This study provides an attractive therapeutic target for treating brain tumors and new insights into mechanisms regulating BTSC dormancy.
Gesehen am 18.09.2019